A PROPOSED COMMUNICATION AUDIT WORK PLAN FOR STUDENT ORGANIZATIONS: THE CASE OF DEMA FIS UINSU - Muhammad Roihan; Abdul Mustaqim (OPINI: Journal of Communication and Social Science, 2026)
Communication continuity is a challenge for student organizations because leadership turnover, limited resources, and academic responsibilities affect information flow and coordination. This study examines the communication conditions of DEMA FIS UINSU and develops a context-specific communication audit work plan. Using a qualitative single-case study design, data were collected from seven administrators through semi-structured interviews, non-participant observations of three organizational forums, and analysis of twelve documents. The findings reveal centralized and sequential information flows, delayed message distribution, unclear task instructions, overlapping responsibilities, uneven participation in meetings, overloaded digital communication channels, informal evaluation practices, and weak institutional memory across leadership periods. Based on these findings, the study formulates a seven-stage audit work plan covering needs analysis, objective and scope determination, team formation, method selection, scheduling and budgeting, data collection and analysis, and reporting with follow-up monitoring. The model provides a framework for improving communication accountability, continuity, and learning in student executive bodies.